Case report: Catastrophic event: neonatal gastric perforation and complication of capillary leak syndrome - Li, Jie; Lu, Hongping; Yu, LinJun; Li, Haiting; Chen, Xiyang; Chen, Caie; Tao, Enfu (Frontiers in Pediatrics, 2023)
Neonatal gastric perforation (NGP) is a rare, but life-threatening condition that can lead to serious conditions, such as capillary leakage syndrome (CLS). Here, we present the case of a preterm male infant with NGP complicated by CLS after stomach repair. The patient was born at 33 2/7 weeks, weighed 1,770 g, and was diagnosed with respiratory distress syndrome. On the fourth day of life, the patient presented with distention and an unstable cardiovascular system. Routine blood tests revealed a white blood cell count of 2.4 × 10 9 /L. Chest and abdominal radiography revealed a pneumoperitoneum, suggesting a gastrointestinal perforation. The patient was urgently transferred to a tertiary hospital for exploratory laparotomy, where a 2 cm diameter perforation was discovered in the stomach wall and subsequently repaired. Pathological findings indicated the absence of a muscular layer in the stomach wall. The patient unexpectedly developed CLS postoperatively, leading to multiorgan dysfunction and eventual death. The underlying pathological mechanism of NGP-induced CLS may be related to severe chemical peritonitis, sepsis, endothelial glycocalyx dysfunction, enhanced systemic inflammation, and translocation of the gut microbiota, causing endothelial hyperpermeability. Notablely, abdominal surgery itself can be a significant triggering factor for CLS occurrence. Complications of NGP and CLS are extremely dangerous. Investigating the mechanism by which NGP triggers CLS could potentially improve the prognosis. Conservative treatment for pneumoperitoneum secondary to gastric perforation may be a reasonable option, especially when the condition of the patient is unstable.